Pengaruh Dosis dan Lama Perendaman Ekstrak Bawang Merah (Allium cepa) Terhadap Stek Batang Tanaman Air Mata Pengantin (Antigonon leptopus) - Bayu Riswandi; Yusmaidar Sepriani; Kamsia Dorliana Sitanggang; Siti Hartati Yusida Saragih (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
This study aims to compare the effect or effectiveness of the bridal tear plant (antigonon leptopus) which was dosed and onion extract (allium cepa) in the soaking process. This research was conducted in the village III Kampung Jawa Pulo Jantan, NA. IX-X sub-district, North Labuhanbatu Utara. This research was conducted from April to June 2021. The design used in the study was a randomized block design (RAK) which involves two (2) factors, including the first factor dosage composition and immersion time (K) with 4 treatments, namely: K0 = Kontrol; K1 = 5 ml; K2 = 10 ml; K3 = 15 ml. Second factor immersion time (L) with 3 treatments, namely: L1 = 8 hours; L2 = 16 hours; L3 = 24 hours. Parameters observed were rod length (cm), number of leaves (sheet), leaf width (cm), stem diameter (mm). As for the result obtained from this study, the highest average was found in the K3L1 treatment, namely a dose of 15 ml with an immersion time 8 hours and the lowest was found in the K0L1 treatment (without treatment). Keywords: Antigonon, Growth, Onion Extract